Study on the Effect of Blood Content on Diffuse Reflectance Spectra of Basal Cell Carcinoma Skin Tissue - Miaoqing Nan; Qingli He (The Scientific World Journal)
Diffuse reflectance spectrum as a noninvasive method has been widely used to study the optical properties of cutaneous skin tissue. In this work, we optimized an eight-layered optical model of basal cell carcinoma skin tissue to study its optical properties. Based on the model, the diffuse reflectance spectra were reconstructed in visible wavelength range by Monte Carlo methods. After different blood contents were added to the optical model, the contribution of blood to diffuese reflectance spectra was investigated theoretically. The ratios of basal cell carcinoma skin and normal skin tissue were also calculated for both experimental result and rebuilt results to testify the theoretical reasonability of the model and methods.